Line Balancing Pada Produksi Kabel Serat Optik Dengan Metode Ranked Positional Weight - Siagian, William Harapan Restadamai; Sulistyo, Arif Budi; Juniarti, Anita Dyah (Universitas Al Azhar Indonesia, 2024)
PT. XYZ produces and manufactures fiber optic cables and pipes in Indonesia. The problem faced in the production section is the imbalance in the work load at each work station. This situation causes bottleneck or accumulation of SF-Product which greatly affects the production operator's performance. The method used is Line Balancing and Ranked Positional Weight to provide the balanced load on all production process factors existing on the production line so as to reduce the difference in operating time between work stations and decrease idle time in the fiber optic cable production process. This study gives the number of machines on the Coloring Line, Buffering Line, Small Jacketing Line, Stranding Line, and Jacketing Line should be 5. There is a combination of tasks on Coloring Line 1 & 2 to meet the needs of Buffering Line 1, and also a combination of tasks on Buffering Line 1 & 2 to meet the needs of Stranding Line 1. In addition, balanced work time assignment in Section 1 is 3115.17 minutes, Section 2 is 2829.428 minutes, Section 3 is 2094.424 minutes, Section 4 is 2094.424 minutes, and Section 5 is 2094.424 minutes.Keywords – Line Balancing, Ranked Positional Weight, Stopwatch Time Study.